Assessing the Suitability of Groundwater for Drinking and Irrigation Using Hydrochemical Indicators in Kirkuk, Northern Iraq - Zakiya Shihab Hamad Al-Obeidi (Lembaga Penelitian dan Pengabdian, Universitas Andalas, 2026)
This study aims to evaluate the groundwater quality of selected wells in Kirkuk City, Northern Iraq, and to assess its suitability for drinking and irrigation purposes using hydrochemical indices. Six groundwater samples were collected during the spring season and analyzed for key physicochemical parameters, including electrical conductivity (EC), total dissolved solids (TDS), pH, major cations (Ca2+, Mg2+, Na+, K+), and major anions (HCO3-, SO42-, Cl-). In addition, irrigation water quality indices such as sodium adsorption ratio (SAR) and sodium percentage (Na%) were calculated. The results revealed considerable spatial variability in groundwater chemistry, with EC and TDS values indicating a range from freshwater to brackish conditions. The hydrochemical facies were predominantly Ca–SO4 and Ca–HCO3 types, reflecting the influence of carbonate and evaporite mineral dissolution. Comparison with Iraqi standards and World Health Organization (WHO) guidelines showed that several samples exceeded permissible limits, particularly in terms of TDS and sulfate concentrations, rendering them unsuitable for drinking purposes. However, the calculated SAR (0.449–1.865) and Na% (13–34%) values indicate that most groundwater samples fall within excellent to good categories for irrigation, with low sodium hazard and minimal impact on soil structure. Salinity remains the primary limiting factor for agricultural use. The study highlights the combined effects of natural hydrogeochemical processes and anthropogenic activities on groundwater quality in the study area. It emphasizes the need for continuous monitoring and the implementation of sustainable groundwater management strategies to ensure safe utilization of this vital resource.